PENGARUH KUALITAS PELAYANAN LEMBAGA AMIL ZAKAT TERHADAP KEPUASAN MUSTAHIK DI LAZISMU (Studi Kasus Mustahik Kecamatan Karangpawitan Kabupaten Garut) - Alviah, Sajaah; Mustikasari, Molly; Haryadi, Yudi (Program Studi Ekonomi Syariah Universitas Muhammadiyah Bandung, 2025)
This research was conducted to determine the Effect of Service Quality of Amil Zakat Institutions on Mustahik Satisfaction at LAZISMU, with mustahik Karangpawitan District as the object of research. The sampling technique used in this study is Accidental Sampling. The population used was 100 people with a sample of 50 people with a descriptive quantitative approach. The data analysis technique used is simple linear regression test. The results of this study indicate that the quality of service of amil zakat institutions has a significant effect on mustahik satisfaction in Karangpawitan District. Based on the results of the t test which shows that the tcount is 5.343> t table 1.677 with a significance of 0.000 <0.05. And from the results of the coefficient of determination (R2) of 0.373. This shows that there is a correlation between the service quality variable (X) and mustahik satisfaction (Y) of 0.373.